(untitled) (Nativa, 2023)
ABSTRACT: This review aims to analyze and synthesize the existing body of literature on biomass resources and their potential for biofuel production. By employing bibliometric methods, this study seeks to identify the key research trends, gaps, and emerging areas of interest in this field. A total of 194 documents deemed appropriate for the study on biomass resources and biofuel potential over the past four decades, i.e., 1980 and 2022 were reviewed. The analysis was done with the VOSviewer software (version 1.6.13). The analysis focused on the bibliographic coupling of countries, sources, co-authorship of authors, citation of documents, and co-occurrence of keywords, which were presented as network visualization maps. The findings revealed that research on biomass resources and biofuel potential is multidisciplinary in character and developing quickly, encompassing nations from around the world. It is evident that Africa lags in this area of research. Therefore, it is recommended that researchers on the continent focus more on this research domain to help address the gap in this research area. This will help researchers and other stakeholders in the energy sector to become familiar with the current and cutting-edge technologies that could promote effective and efficient biomass resources and biofuel potential. Keywords: biomass; biofuel; agricultural waste; network visualization maps; VOSviewer. Tendências de pesquisa em recursos de biomassa e potencial de biocombustíveis: uma análise bibliométrica RESUMO: Esta revisão visa analisar e sintetizar o corpo de literatura existente sobre recursos de biomassa e seu potencial para a produção de biocombustíveis. Ao empregar métodos bibliométricos, este estudo procura identificar as principais tendências de pesquisa, lacunas e áreas emergentes de interesse neste campo. Foram revisados 194 documentos considerados adequados para o estudo dos recursos de biomassa e do potencial de biocombustíveis nas últimas quatro décadas, ou seja, 1980 e 2022. A análise foi feita com o software VOSviewer (versão 1.6.13). A análise centrou-se no acoplamento bibliográfico de países, fontes, coautoria de autores, citação de documentos e coocorrência de palavras-chave, que foram apresentados como mapas de visualização em rede. Os resultados revelaram que a pesquisa sobre recursos de biomassa e potencial de biocombustíveis é de caráter multidisciplinar e está se desenvolvendo rapidamente, abrangendo nações de todo o mundo. É evidente que a África está atrasada nesta área de pesquisa. Portanto, recomenda-se que os pesquisadores do continente se concentrem mais neste domínio de pesquisa para ajudar a preencher a lacuna nesta área de pesquisa. Isso ajudará os pesquisadores e outras partes interessadas no setor de energia a se familiarizarem com as tecnologias atuais e de ponta que podem promover recursos de biomassa eficazes e eficientes e o potencial de biocombustíveis. Palavras-chaves: biomassa; biocombustível; resíduos agrícolas; mapas de visualização de rede; VOSviewer.